Edukasi Cuci Tangan Pakai Sabun sebagai Upaya Pencegahan Penyakit pada Siswa SDN 84 Pare-Pare - Herman; Aida Ayu Chandrawati; Ega Delva; Azizah, Nurul (Education and Talent Development Center Indonesia, 2025)
Infectious diseases among elementary school children remain high, primarily due to inadequate handwashing habits with soap. This community service activity aimed to improve the knowledge and skills of SDN 84 Pare-Pare students regarding the importance of handwashing with soap as a disease prevention measure. The program was conducted on November 6, 2025, involving 35 students and 5 teachers. Methods included educational lectures, interactive discussions, demonstrations of proper handwashing steps, and educational games. The results showed high participant enthusiasm and improved understanding of the six-step handwashing procedure. Teachers also committed to integrating regular handwashing practices into daily routines. These findings indicate that an educational and interactive approach is effective in promoting clean and healthy behaviors within the school environment.